1992
DOI: 10.1007/bf02893007
|View full text |Cite
|
Sign up to set email alerts
|

Internal wave characteristics in the eastern Arabian Sea during summer monsoon

Abstract: The time series BT profiles and surface winds and atmospheric pressure, collected in the deep waters off Ratnagiri and Karwar during summer monsoon were utilized to document the characteristics of internal waves (IW). Low-frequency (~< 2 cycle per day (cpd)) IW off Ratnagiri are found to propagate at 83 cm/s with wavelengths of 45 km and wave heights upto 40 m. These parameters for high-frequency (> 2 cpd) IW off Karwar correspond to 99cm/s, 3km and 23m. The IW off Karwar appear to leave the station at 70 ~ (+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Until recently, studies on internal tides in the AS remained remarkably limited and mostly based on observations (Murthy et al, 1992;Shenoi et al, 2005). One example of successful internal tide amplitude recordings is from an array of four moorings deployed by the Russian R/V Vityaz in 1967, which recorded the amplitudes of internal tides in the upper 200 m. During the AS Mixed Layer Dynamics Experiment (Woods Hole Oceanographic Institution) in 1994, a mooring deployed at 15°30'N, 61°30'E, captured high internal tide amplitudes up to 25-30 m at a depth of 300 m. Based on in-situ data, Kumar et al (2010) proposed that temperature fluctuations attributed to internal tides are associated with a thermocline gradient in the northeastern AS.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, studies on internal tides in the AS remained remarkably limited and mostly based on observations (Murthy et al, 1992;Shenoi et al, 2005). One example of successful internal tide amplitude recordings is from an array of four moorings deployed by the Russian R/V Vityaz in 1967, which recorded the amplitudes of internal tides in the upper 200 m. During the AS Mixed Layer Dynamics Experiment (Woods Hole Oceanographic Institution) in 1994, a mooring deployed at 15°30'N, 61°30'E, captured high internal tide amplitudes up to 25-30 m at a depth of 300 m. Based on in-situ data, Kumar et al (2010) proposed that temperature fluctuations attributed to internal tides are associated with a thermocline gradient in the northeastern AS.…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal variations in stratification possibly influence the properties of internal tides in this basin. Previous studies on internal tides in the Arabian Sea were markedly limited and mostly based on in situ observations [30,31]. However, due to the development of global satellite observation networks, several studies recently indicated that the Arabian Sea is a hotspot of internal tides [24,32].…”
Section: Introductionmentioning
confidence: 99%